Transfer of the Honduran species Calathea carolineae to the genus Goeppertia (Marantaceae) - Braga, Joao Marcelo Alvarenga (Phytotaxa, 2014)
Calathea carolineae is herein transferred to Goeppertia. This genus has recently been redefined morphologically and, hence, incorporates most species previously described as Calathea.